Shaping the key themes in zakat accounting research: a bibliometric exploration - Naiimi, Nazirah; Mohamad Fadzillah, Fazni; Abdul Wahid, Nor Hashimah; Mohd Noor, Marjan; Wan Ya, Wan Kamarul Hazim (Universiti Teknologi MARA, Perlis, 2025)
Zakat accounting plays a vital role in enhancing transparency, accountability and ethical financial reporting within Islamic financial systems. This study examines the development and scholarly progress of research publications on zakat accounting through a bibliometric analysis of data extracted from the Scopus database covering the period from 1991 to 2024. Using descriptive bibliometric methods, the study explores publication trends by analyzing publication years, leading authors, sources, institutions, countries and document types. The analysis highlights a notable growth in zakat accounting research, especially from 2016 onwards, with most contributions stemming from Malaysia and Indonesia. The findings reveal dominant publication sources, such as the Journal of Islamic Accounting and Business Research, and prominent affiliations, including the International Islamic University Malaysia. By applying a scientific and statistical approach, this study contributes to understanding the evolution and impact of zakat accounting research. It also provides a foundation for future academic work and helps to establish a research agenda that supports broader integration of Islamic principles in modern financial reporting.